What ethnography sees that diagnosis misses: A clinical commentary on borderline personality disorder and ‘structures of care and credibility’ - Shaun Halovic (The Australian Journal of Anthropology, 2026)
Abstract In their recent article in The Australian Journal of Anthropology , Ira Parker Vaughan (2025) presents a rich ethnographic account of Anika and Milan that raises broader questions about how complex forms of suffering are recognised and interpreted. This commentary argues that the significance of Vaughan's article extends beyond the particulars of the case itself. Rather than treating Anika as a subject for retrospective psychiatric diagnosis, I suggest that the ethnography illustrates why certain forms of psychological distress resist easy categorisation within conventional clinical frameworks. Drawing on contemporary research into borderline personality disorder (BPD), I explore how phenomena commonly associated with borderline personality organisation (including affective instability, identity disturbance, rejection sensitivity, unstable interpersonal relationships, fluctuating caregiving behaviours, contradictory help‐seeking, and oscillations between dependency and hostility) often emerge not as discrete symptoms but as relational patterns distributed across everyday life. Such patterns are difficult to recognise within the episodic and symptom‐focused encounters that characterise much clinical practice, yet they become visible through the temporal depth and contextual richness of ethnographic observation. The value of Vaughan's account lies in demonstrating how behaviours that may appear fragmented, contradictory, or implausible in clinical settings become intelligible when situated within histories of trauma, caregiving, social obligation, and interpersonal relationships. The commentary argues that ethnography offers a valuable complement to psychiatry by revealing forms of distress that unfold between people rather than solely within individuals. More broadly, it asks what anthropology can teach clinicians about recognising disorders with defining features that are relational, developmental, and socially embedded.